2000
DOI: 10.1016/s0002-9440(10)64943-7
|View full text |Cite
|
Sign up to set email alerts
|

Activated Leukocyte Cell Adhesion Molecule/CD166, a Marker of Tumor Progression in Primary Malignant Melanoma of the Skin

Abstract: Expression of activated leukocyte cell adhesion molecule (ALCAM)/CD166 correlates with the aggregation and metastatic capacity of human melanoma cell lines (Am J Pathol 1998, 152:805-813). Immunohistochemistry on a series of human melanocytic lesions reveals that ALCAM expression correlates with melanoma progression. Most nevi (34/38) and all thin melanomas studied (Clark levels I and II) did not express ALCAM. In contrast, immunoreactivity was detected in the invasive, vertical growth phase of 2 of the 13 Cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
153
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(170 citation statements)
references
References 22 publications
16
153
0
1
Order By: Relevance
“…12 Similar to our findings, nevi, when positive, showed staining limited to the junctional component or nevic nests in the superficial papillary dermis. The authors speculate that CD166 plays an important role in melanoma cell invasion and melanoma progression.…”
supporting
confidence: 91%
“…12 Similar to our findings, nevi, when positive, showed staining limited to the junctional component or nevic nests in the superficial papillary dermis. The authors speculate that CD166 plays an important role in melanoma cell invasion and melanoma progression.…”
supporting
confidence: 91%
“…It has been implicated in pathologic states, such as cancer metastasis, but its role remains inconsistent. ALCAM was found to be upregulated in melanoma, colon cancer, esophageal squamous cell carcinoma, and gastric cancer and plays a role in promoting motility and migration (40)(41)(42)(43). In prostate carcinoma, ALCAM was upregulated in low-grade tumors, but downregulated in high-grade tumors (44).…”
Section: Discussionmentioning
confidence: 99%
“…The initial studies that identified a role for ALCAM in human malignancies were performed in melanoma (4,5). Over the last decade, alterations in ALCAM expression have been described in several other malignancies including bladder (6), colorectal (7), esophageal squamous cell (8), pancreatic (9), oral squamous cell (10) and ovarian cancer (11), neuroblastoma (12), prostate (13) and breast cancer (14,15).…”
Section: Introductionmentioning
confidence: 99%